2020
DOI: 10.3390/ijerph17186572
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress, Stigma, Traumatic Stress Levels and Coping Responses amongst Residents in Training across Multiple Specialties during COVID-19 Pandemic—A Longitudinal Study

Abstract: This study aimed to explore changes in psychological responses (perceived stress, traumatic stress, stigma, coping) over time in residents, as well as their predictors. The level of perceived stress, traumatic stress, stigma, and coping responses were assessed using the Perceived Stress Scale, Impact of Event-Revised, Healthcare Workers Stigma Scale, and Brief Coping Orientation to Problems Experienced (COPE) Inventory, respectively. We collected responses from 274 residents at baseline and 221 residents at 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
115
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 22 publications
6
115
1
2
Order By: Relevance
“…Most of these studies have been cross-sectional, although some longitudinal studies currently exist. In comparison, our findings of decreasing distress over time are like those observed among resident physicians in Singapore [ 27 ]. There, lower stress was observed at three months, and significant predictors included living alone, less ability to problem solve, and seeking social support [ 27 ]).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Most of these studies have been cross-sectional, although some longitudinal studies currently exist. In comparison, our findings of decreasing distress over time are like those observed among resident physicians in Singapore [ 27 ]. There, lower stress was observed at three months, and significant predictors included living alone, less ability to problem solve, and seeking social support [ 27 ]).…”
Section: Discussionsupporting
confidence: 85%
“…In comparison, our findings of decreasing distress over time are like those observed among resident physicians in Singapore [ 27 ]. There, lower stress was observed at three months, and significant predictors included living alone, less ability to problem solve, and seeking social support [ 27 ]). Our findings also echo the pattern observed in the Chinese general population, where psychiatric distress decreased significantly between the COVID-19 onset and peak number of cases one month later [ 28 ].…”
Section: Discussionsupporting
confidence: 85%
“…Fourteen studies identified specific coping mechanisms employed by HCWs during the pandemic (Blanco-Donoso et al ., 2020; Cai, 2020; Chen et al ., 2020; Chew et al ., 2020; Dong et al ., 2020; Giusti et al ., 2020; Labrague & De los Santos, 2020; Maraqa et al ., 2020; Mi et al ., 2020; Nie et al., 2020; Salman et al, 2020; Shechter et al ., 2020; Vagni et al ., 2020; Xiao et al ., 2020). During the pandemic, HCWs utilized both negative and positive coping styles to manage stress.…”
Section: Methodsmentioning
confidence: 99%
“…Among these ten studies reporting specific coping styles among HCWs during the pandemic, eleven quantitative studies (Cai, 2020; Blanco-Donoso et al ., 2020; Chew et al ., 2020; Dong et al ., 2020; Giusti et al ., 2020; Labrague & De los Santos, 2020; Nie et al ., 2020; Xiao et al ., 2020; Chen et al ., 2020; Maraqa et al ., 2020; Vagni et al ., 2020) indicated that HCWs use support from and communication with family, friends, and colleagues as their primary coping mechanisms to manage the adverse mental health consequences of the COVID-19 pandemic. Religious coping mechanisms such as praying were reported as an important coping mechanism in three cross-sectional studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation